Patterns of antibody binding to aquaporin-4 isoforms in neuromyelitis optica. - Simone Mader; Andreas Lutterotti; Franziska Di Pauli; Bettina Kuenz; Kathrin Schanda; Fahmy Aboul-Enein; Michael Khalil; Maria K Storch; Sven Jarius; Wolfgang Kristoferitsch; Thomas Berger; Markus Reindl (PLoS ONE, 2010)
BACKGROUND: Neuromyelitis optica (NMO), a severe demyelinating disease, represents itself with optic neuritis and longitudinally extensive transverse myelitis. Serum NMO-IgG autoantibodies (Abs), a specific finding in NMO patients, target the water channel protein aquaporin-4 (AQP4), which is expressed as a long (M-1) or a short (M-23) isoform. METHODOLOGY/PRINCIPAL FINDINGS: The aim of this study was to analyze serum samples from patients with NMO and controls for the presence and epitope specificity of IgG and IgM anti-AQP4 Abs using an immunofluorescence assay with HEK293 cells expressing M-1 or M-23 human AQP4. We included 56 patients with definite NMO (n = 30) and high risk NMO (n = 26), 101 patients with multiple sclerosis, 27 patients with clinically isolated syndromes (CIS), 30 patients with systemic lupus erythematosus (SLE) or Sjögren's syndrome, 29 patients with other neurological diseases and 47 healthy controls. Serum anti-AQP4 M-23 IgG Abs were specifically detected in 29 NMO patients, 17 patients with high risk NMO and two patients with myelitis due to demyelination (CIS) and SLE. In contrast, IgM anti-AQP4 Abs were not only found in some NMO and high risk patients, but also in controls. The sensitivity of the M-23 AQP4 IgG assay was 97% for NMO and 65% for high risk NMO, with a specificity of 100% compared to the controls. Sensitivity with M-1 AQP4 transfected cells was lower for NMO (70%) and high risk NMO (39%). The conformational epitopes of M-23 AQP4 are the primary targets of NMO-IgG Abs, whereas M-1 AQP4 Abs are developed with increasing disease duration and number of relapses. CONCLUSIONS: Our results confirm M-23 AQP4-IgG Abs as reliable biomarkers in patients with NMO and high risk syndromes. M-1 and M-23 AQP4-IgG Abs are significantly associated with a higher number of relapses and longer disease duration.